Modern Labour Economics: The Neoclassical Paradigm with Institutional Theories - Brozova, Dagmar (European Scientific Journal, ESJ, 2016)
The growing role of institutions and their influence on the labour market outcomes, i.e. wage rates and labour allocation, has been among the most significant characteristic features of labour markets in recent decades. Labour market economics built its paradigm on the principles of marginalism, which brought suitable instruments for analysis of market agents´ individual decisions capable of achieving effective solutions. Smith´s “invisible hand” has gradually been limited by institutional interventions – by governments, corporations and trade unions with government legislation, corporate personnel policies and collective bargaining. The expanding regulatory interventions into the labour market and the effort to explain the reality leads inevitably to the fact that modern labour market economics incorporates more and more institutional theories. The contribution outlines the gradual invasion of neoinstitutional topics and theories into the neoclassical labour market paradigm and it analyses the differences in the neoclassical and neoinstitutional interpretation of labour markets’ functioning. The recent discussion on the consequences for labour market economics theory is presented. A conclusion about the gradual direction towards a changed paradigm of labour market economics is presented.